Digitizing the Unexplored: Bridging the Concrete Experience and Abstract Geometry Through Physical Experiments - Alaçam, Sema; GÜZELCİ, ORKAN ZEYNEL (My University, 2016)
Ways of promoting creative approaches in the context of embedding digital design approaches in education are increasingly becoming a popular topic in architecture schools. On one hand, digital design methods, approaches and tools are diversified, while on the other hand, the danger for students losing control over the design process by appears as a new phenomenon. We argue that experiential dimensions of empirical observation conducted with physical experimentation might be helpful for students to comprehend digital topics creatively. With a particular emphasis on engagement of physical experimentation and computational thinking, this study aims to present a pedagogical model which has been applied from 2014 to 2016 within a postgraduate course. The potentials and limitations of the introduced pedagogical model are investigated through students' bottom-up and top-down algorithm development processes and the outcomes of the digital modelling exercises.
Keywords: pedagogical model; dynamic process; physical experiment; computational thinking